Solid oxide fuel cell and method for producing same

A symmetrical structure with mixed layers and supports in solid oxide fuel cells addresses thermal expansion issues, reducing warpage and preventing short circuits, ensuring stable and efficient power generation.

JP7607393B2Active Publication Date: 2024-12-27TAIYO YUDEN KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021046531
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-19
Publication Date
2024-12-27
Estimated Expiration
2041-03-19

AI Technical Summary

Technical Problem

Solid oxide fuel cells face issues with warping and short circuits due to differences in thermal expansion coefficients between the anode and cathode, leading to structural instability and potential cracking during firing.

Method used

A symmetrical structure is implemented with mixed layers and supports on either side of the solid electrolyte layer, where the outer peripheries of the cathode and second support are inward from the anode and first support, and specific ratios and void shapes are used to minimize thermal mismatch and prevent short circuits.

Benefits of technology

The solution effectively reduces warpage to less than 4% and prevents short circuits, allowing for stable operation and improved adhesion between layers, enhancing mechanical strength and power generation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607393000003
    Figure 0007607393000003
  • Figure 0007607393000004
    Figure 0007607393000004
  • Figure 0007607393000005
    Figure 0007607393000005
Patent Text Reader

Abstract

To provide a solid oxide type fuel cell which can suppress the occurrence of short circuit, and a manufacturing method thereof.SOLUTION: A solid oxide type fuel cell comprises: a solid electrolyte layer; an anode provided on a first face of the solid electrolyte layer, and having a porous body containing electron-conducting ceramics and oxide ion-conducting ceramics; a first mixture layer provided on the anode and having a structure in which the metal materials and ceramic materials are mixed; a first support body provided on the first mixture layer and having metal as a primary component; a cathode provided on a second face of the solid electrolyte layer and having a porous body including electron-conducting ceramics and oxide ion-conducting ceramics; a second mixture layer provided on the cathode and having a structure in which metal materials and ceramic materials are mixed; and a second support body provided on the second mixture layer and having metal as a primary component. One of an outer periphery of the anode, first mixture layer and first support body, and an outer periphery of the cathode, second mixture layer and second support body is located inside the other.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid oxide fuel cell and a method for producing the same. [Background technology]

[0002] In order to develop a solid oxide fuel cell system that can be used in automobiles, etc., it is necessary to develop a cell that can withstand vibration and does not crack even when the temperature is raised rapidly. Therefore, metal-supported solid oxide fuel cells supported by a metal support have been developed (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2004-512651 [Patent Document 2] JP 2020-21646 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, due to the difference in structure between the anode and the cathode, there is a risk of a difference in thermal expansion coefficient, which may cause warping of the solid oxide fuel cell during firing. Therefore, it is conceivable to make the anode and cathode have a symmetrical structure in order to reduce the difference in structure between the anode and the cathode. However, there is a risk of a short circuit occurring between the metal support on the anode side and the metal support on the cathode side during firing.

[0005] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a solid oxide fuel cell capable of suppressing the occurrence of short circuits, and a method for manufacturing the same. [Means for solving the problem]

[0006] The solid oxide fuel cell according to the present invention comprises a solid electrolyte layer containing a solid oxide having oxide ion conductivity, an anode provided on a first surface of the solid electrolyte layer and having a porous body containing an electron conductive ceramic and an oxide ion conductive ceramic, the porous body having an anode catalyst, a first mixed layer provided on a surface of the anode opposite to the solid electrolyte layer and having a structure in which a metal material and a ceramic material are mixed, a first support provided on the surface of the first mixed layer opposite to the solid electrolyte layer and mainly composed of a metal, and a second support provided on a second surface of the solid electrolyte layer and having an electron conductive ceramic. The anode comprises a porous body containing a ceramic and an oxide ion conductive ceramic, the porous body having a cathode catalyst; a second mixed layer provided on the surface of the cathode opposite the solid electrolyte layer and having a structure in which a metal material and a ceramic material are mixed; and a second support provided on the surface of the second mixed layer opposite the solid electrolyte layer and containing a metal as a main component, wherein one of the outer periphery of the anode, the first mixed layer, and the first support, and the outer periphery of the cathode, the second mixed layer, and the second support, is located inward relative to the other.

[0007] In the above solid oxide fuel cell, one of the outer periphery of the anode, the first mixed layer, and the first support, and the outer periphery of the cathode, the second mixed layer, and the second support may be located 1 mm or more inward from the other.

[0008] The solid oxide fuel cell may have a generally rectangular shape in a plan view, and when the length from the outer periphery of the anode, the first mixed layer, and the first support to the outer periphery of the cathode, the second mixed layer, and the second support is defined as a length a, and the length of one side of the solid oxide fuel cell is defined as a length b, a / b may be 1 / 10 or less.

[0009] In the solid oxide fuel cell, the cathode, the second mixed layer and the second support may be located inwardly with respect to the outer periphery of the anode, the first mixed layer and the first support.

[0010] The solid oxide fuel cell may have a warpage of less than 4%.

[0011] In a cross section including the stacking direction of the above solid oxide fuel cell, if the length of the gaps in each layer in the direction in which each layer extends is defined as length c and the height in the stacking direction is defined as height d, the average c / d of each gap in the cathode may be greater than the average c / d of each gap in the anode, the average c / d of each gap in the second mixed layer may be greater than the average c / d of each gap in the first mixed layer, and the average c / d of each gap in the second support may be greater than the average c / d of each gap in the first support.

[0012] In the solid oxide fuel cell, the average value of c / d of each of the voids in the cathode, the second mixed layer and the second support may be greater than 1 and less than 3.

[0013] In the solid oxide fuel cell, the anode catalyst is Ni and GDC, and the cathode catalyst is PrO x , LSM, LSC, and GDC.

[0014] In the solid oxide fuel cell, the anode catalyst and the cathode catalyst may each have an average particle size of 100 nm or less.

[0015] In the above solid oxide fuel cell, the porosity of the first support, the porosity of the first mixed layer, and the porosity of the anode may have a relationship of first support > first mixed layer > anode, and the porosity of the second support, the porosity of the second mixed layer, and the porosity of the cathode may have a relationship of second support > second mixed layer > cathode.

[0016] In the above solid oxide fuel cell, the thickness of the first support, the thickness of the first mixed layer, and the thickness of the anode may have a relationship of first support > first mixed layer > anode, and the thickness of the second support, the thickness of the second mixed layer, and the thickness of the cathode may have a relationship of second support > second mixed layer > cathode.

[0017] The method for manufacturing a solid oxide fuel cell according to the present invention is characterized by comprising the steps of: preparing a laminate comprising a support green sheet containing metal powder, a mixed layer green sheet containing ceramic material powder and metal material powder, an electrode green sheet containing electronically conductive ceramic material powder and oxide ion conductive ceramic material powder, and an electrolyte green sheet containing solid oxide material powder having oxide ion conductivity; and printing a slurry containing electronically conductive ceramic material powder and oxide ion conductive ceramic material powder, a slurry containing ceramic material powder and metal material powder, and a slurry containing metal powder, inward from the outer periphery of the electrolyte green sheet, followed by firing. Effect of the Invention

[0018] According to the present invention, it is possible to provide a solid oxide fuel cell capable of suppressing the occurrence of short circuits and a method for manufacturing the same. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1A is a schematic cross-sectional view illustrating a stacked structure of a solid oxide fuel cell, and FIG. 1B is a plan view of the fuel cell. [Diagram 2] FIG. 2 is an enlarged cross-sectional view illustrating details of a first support, a first mixed layer, an anode, a cathode, a second mixed layer, and a second support. [Diagram 3] FIG. 13 is a diagram for explaining warping of a fuel cell. [Figure 4] FIG. 13 is a diagram illustrating an example of the shape of a gap. [Diagram 5] 1A and 1B are diagrams illustrating examples of the shape of a void. [Figure 6] 13(a) and 13(b) are diagrams for explaining a method for measuring the length c and the height d. [Figure 7] FIG. 2 is a diagram illustrating a flow of a method for manufacturing a fuel cell. [Figure 8] FIG. 13 is a diagram showing the relationship between the heat treatment temperature at which gas leakage was detected and the c / d value. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, an embodiment will be described with reference to the drawings.

[0021] FIG. 1(a) is a schematic cross-sectional view illustrating a stack structure of a solid oxide fuel cell 100. FIG. 1(b) is a plan view of the fuel cell 100. As illustrated in FIG. 1(a), the fuel cell 100 has an anode 30 on a first surface of a solid electrolyte layer 40, a first mixed layer 20 on the surface of the anode 30 opposite to the solid electrolyte layer 40, a first support 10 on the surface of the first mixed layer 20 opposite to the solid electrolyte layer 40, a cathode 50 on a second surface of the solid electrolyte layer 40, a second mixed layer 60 on the surface of the cathode 50 opposite to the solid electrolyte layer 40, and a second support 70 on the surface of the second mixed layer 60 opposite to the solid electrolyte layer 40. A fuel cell stack may be formed by stacking a plurality of fuel cells 100.

[0022] As illustrated in FIG. 1(a) and FIG. 1(b), the first support 10, the first mixed layer 20, the anode 30, and the solid electrolyte layer 40 have a rectangular shape (for example, a square shape) of approximately the same size. The positions of the outer peripheries (side faces) of the first support 10, the first mixed layer 20, the anode 30, and the solid electrolyte layer 40 are approximately aligned. Therefore, the outer peripheries of the first support 10, the first mixed layer 20, the anode 30, and the solid electrolyte layer 40 form an outer periphery surface. The length of one side of the rectangular shape of the first support 10, the first mixed layer 20, the anode 30, and the solid electrolyte layer 40 is referred to as length b.

[0023] The cathode 50, the second mixed layer 60, and the second support 70 have a rectangular shape (for example, a square shape) of approximately the same size. The positions of the outer peripheries (side faces) of the cathode 50, the second mixed layer 60, and the second support 70 are approximately aligned. Therefore, the outer peripheries of the cathode 50, the second mixed layer 60, and the second support 70 form an outer periphery surface.

[0024] The outer peripheral surfaces of the cathode 50, the second mixed layer 60, and the second support 70 are located inward of the outer peripheral surfaces of the first support 10, the first mixed layer 20, the anode 30, and the solid electrolyte layer 40. The length from the outer peripheral surfaces of the first support 10, the first mixed layer 20, the anode 30, and the solid electrolyte layer 40 to the outer peripheral surfaces of the cathode 50, the second mixed layer 60, and the second support 70 is referred to as length a.

[0025] 1(a) and 1(b), the outer peripheral surfaces of the cathode 50, the second mixed layer 60, and the second support 70 are located inward of the outer peripheral surfaces of the first support 10, the first mixed layer 20, the anode 30, and the solid electrolyte layer 40, but the outer peripheral surfaces of the first support 10, the first mixed layer 20, the anode 30, and the solid electrolyte layer 40 may be located inward of the outer peripheral surfaces of the cathode 50, the second mixed layer 60, and the second support 70. In this case, the outer periphery of the solid electrolyte layer 40 approximately coincides with the outer periphery of the cathode 50, the second mixed layer 60, and the second support 70.

[0026] The solid electrolyte layer 40 is a dense solid layer that is gas impermeable and mainly made of a solid oxide having oxide ion conductivity. The solid electrolyte layer 40 is preferably made of scandia-yttria stabilized zirconium oxide (ScYSZ) or the like. 2 O 3 +Sc 2 O 3 The oxide ion conductivity is highest when the concentration is between 6 mol% and 15 mol%, and it is desirable to use a material with this composition. The thickness of the solid electrolyte layer 40 is preferably 20 μm or less, and more preferably 10 μm or less. The thinner the electrolyte, the better, but in order to manufacture the electrolyte so that gas does not leak from both sides, a thickness of 1 μm or more is desirable.

[0027] FIG. 2 is an enlarged cross-sectional view illustrating details of the first support 10, the first mixed layer 20, the anode 30, the cathode 50, the second mixed layer 60, and the second support 70.

[0028] The first support 10 is a member that has gas permeability and is capable of supporting the first mixed layer 20, the anode 30, the solid electrolyte layer 40, the cathode 50, and the second mixed layer 60. The first support 10 is a porous metal body, such as a porous Fe—Cr alloy body.

[0029] The anode 30 is an electrode having electrode activity as an anode, and has a porous body (electrode skeleton) of a ceramic material. The porous body does not contain metal components. In this configuration, the decrease in the porosity of the anode caused by the coarsening of the metal components during firing in a high-temperature reducing atmosphere is suppressed. In addition, alloying with the metal components of the first support 10 is suppressed, and the decrease in catalytic function is suppressed.

[0030] The porous body of the anode 30 has electronic conductivity and oxide ion conductivity. The anode 30 contains an electronically conductive ceramic 31. The electronically conductive ceramic 31 may be, for example, a ceramic having a composition formula of ABO 3 In the present invention, a perovskite oxide represented by the formula (1) can be used, in which the A site is at least one selected from the group consisting of Ca, Sr, Ba, and La, and the B site is at least one selected from Ti and Cr. The molar ratio of the A site to the B site may be B≧A. Specifically, the electron conductive ceramic 31 may be LaCrO 3 based material, SrTiO 3 Materials such as those based on fluorine can be used.

[0031] The porous body of the anode 30 contains an oxide ion conductive ceramic 32. The oxide ion conductive ceramic 32 is ScYSZ or the like. For example, scandia (Sc 2 O 3 ) is 5 mol% to 16 mol%, and yttria (Y 2 O 3It is preferable to use ScYSZ having a composition range of 1 mol% to 3 mol% of scandia and yttria. It is more preferable to use ScYSZ having a total amount of scandia and yttria added of 6 mol% to 15 mol%. This is because the oxide ion conductivity is highest within this composition range. The oxide ion conductive ceramic 32 is, for example, a material having an oxide ion transport number of 99% or more. GDC or the like may be used as the oxide ion conductive ceramic 32. In the example of FIG. 2, the same solid oxide as the solid oxide contained in the solid electrolyte layer 40 is used as the oxide ion conductive ceramic 32.

[0032] As shown in FIG. 2, in the anode 30, for example, an electron conductive ceramic 31 and an oxide ion conductive ceramic 32 form a porous body. A plurality of voids are formed by this porous body. The porosity of the porous body is preferably 20% or more in terms of area ratio when viewed in cross section. An anode catalyst is supported on the surface of the porous body in the void portion. Therefore, in the porous body formed spatially continuously, a plurality of anode catalysts are spatially dispersed and arranged. It is preferable to use a composite catalyst as the anode catalyst. For example, it is preferable that an oxide ion conductive ceramic 33 and a catalytic metal 34 are supported on the surface of the porous body as the composite catalyst. For example, Y-doped BaCe 1-x Zr x O 3 (BCZY, x=0~1), Y-doped SrCe 1-x Zr x O 3 (SCZY, x=0~1), Sr-doped LaScO 3(LSS), GDC, etc. can be used. Ni, etc. can be used as the catalytic metal 34. The oxide ion conductive ceramics 33 may have the same composition as the oxide ion conductive ceramics 32, or may have a different composition. The metal functioning as the catalytic metal 34 may be in the form of a compound when power is not being generated. For example, Ni may be in the form of NiO (nickel oxide). During power generation, these compounds are reduced by a reducing fuel gas supplied to the anode 30, and take the form of a metal that functions as an anode catalyst.

[0033] The first mixed layer 20 contains a metal material 21 and a ceramic material 22. In the first mixed layer 20, the metal material 21 and the ceramic material 22 are randomly mixed. Therefore, a structure in which a layer of the metal material 21 and a layer of the ceramic material 22 are laminated is not formed. A plurality of voids are also formed in the first mixed layer 20. The metal material 21 is not particularly limited as long as it is a metal. In the example of FIG. 2, the same metal material as that of the first support 10 is used as the metal material 21. The ceramic material 22 may be an electron conductive ceramic 31, an oxide ion conductive ceramic 32, or the like. For example, the ceramic material 22 may be ScYSZ, GDC, SrTiO 3 based material, LaCrO 3 Materials such as SrTiO 3 Materials based on LaCrO 3 Since the base material has high electronic conductivity, the ohmic resistance in the first mixed layer 20 can be reduced.

[0034] The cathode 50 is an electrode having electrode activity as a cathode, and has a porous body (electrode skeleton) of a ceramic material. The porous body does not contain a metal component. The porous body of the cathode 50 has electronic conductivity and oxide ion conductivity. The cathode 50 contains an electronically conductive ceramic 51. The electronically conductive ceramic 51 may be, for example, a ceramic having a composition formula of ABO 3In the present invention, a perovskite oxide represented by the formula (1) can be used, in which the A site is at least one selected from the group consisting of Ca, Sr, Ba, and La, and the B site is at least one selected from Ti and Cr. The molar ratio of the A site to the B site may be B≧A. Specifically, the electron conductive ceramic 51 may be LaCrO 3 based material, SrTiO 3 The electron conductive ceramic 51 preferably contains the same components as the electron conductive ceramic 31, and preferably has the same composition ratio as the electron conductive ceramic 31.

[0035] The porous body of the cathode 50 contains an oxide ion conductive ceramic 52. The oxide ion conductive ceramic 52 is ScYSZ or the like. For example, scandia (Sc 2 O 3 ) is 5 mol% to 16 mol%, and yttria (Y 2 O 3 It is preferable to use ScYSZ having a composition range of 1 mol% to 3 mol% of yttria. It is more preferable to use ScYSZ having a total amount of scandia and yttria added of 6 mol% to 15 mol%. This is because the oxide ion conductivity is highest in this composition range. The oxide ion conductive ceramic 52 is, for example, a material having an oxide ion transport number of 99% or more. GDC or the like may be used as the oxide ion conductive ceramic 52. It is preferable that the oxide ion conductive ceramic 52 contains the same components as the oxide ion conductive ceramic 32 and has the same composition ratio. In the example of FIG. 2, the same solid oxide as the solid oxide contained in the solid electrolyte layer 40 is used as the oxide ion conductive ceramic 52.

[0036] As shown in FIG. 2, in the cathode 50, for example, an electron conductive ceramic 51 and an oxide ion conductive ceramic 52 form a porous body. A plurality of voids are formed by this porous body. The porosity of the porous body is preferably 20% or more in terms of area ratio when viewed in cross section. A cathode catalyst 53 is supported on the surface of the porous body in the void portion. Therefore, a plurality of cathode catalysts 53 are arranged in a spatially dispersed manner in the spatially continuous porous body. Praseodymium oxide (PrO x ), LSM (lanthanum strontium manganite), LSC (lanthanum strontium cobaltite), etc. can be used. LSM is Sr-doped LaMnO 3 LSM is a Sr-doped LaCoO 3 It is a material based on

[0037] The second mixed layer 60 contains a metal material 61 and a ceramic material 62. In the second mixed layer 60, the metal material 61 and the ceramic material 62 are randomly mixed. Therefore, a structure in which a layer of the metal material 61 and a layer of the ceramic material 62 are laminated is not formed. A plurality of voids are also formed in the second mixed layer 60. The metal material 61 is not particularly limited as long as it is a metal. In the example of FIG. 2, the same metal material as that of the second support 70 is used as the metal material 61. The ceramic material 62 may be an electron conductive ceramic 51, an oxide ion conductive ceramic 52, or the like. For example, the ceramic material 62 may be ScYSZ, GDC, SrTiO 3 based material, LaCrO 3 Materials such as SrTiO 3 Materials based on LaCrO 3 Since the base material has high electronic conductivity, the ohmic resistance in the second mixed layer 60 can be reduced.

[0038] The second support 70 is a member that has gas permeability and is capable of supporting the second mixed layer 60, the cathode 50, the solid electrolyte layer 40, the anode 30, and the first mixed layer 20. The second support 70 is a porous metal body, such as a porous Fe—Cr alloy body.

[0039] The fuel cell 100 generates power by the following action. An oxidant gas containing oxygen, such as air, is supplied to the second support 70. The oxidant gas reaches the cathode 50 through the second support 70 and the second mixed layer 60. At the cathode 50, the oxygen that has reached the cathode 50 reacts with electrons supplied from an external electric circuit to become oxide ions. The oxide ions move to the anode 30 side through the solid electrolyte layer 40. On the other hand, a fuel gas containing hydrogen, such as hydrogen gas or reformed gas, is supplied to the first support 10. The fuel gas reaches the anode 30 through the first support 10 and the first mixed layer 20. The hydrogen that has reached the anode 30 releases electrons at the anode 30 and reacts with oxide ions that have been conducted through the solid electrolyte layer 40 from the cathode 50 side to produce water (H 2 O). The emitted electrons are extracted to the outside by an external electric circuit. The extracted electrons are supplied to the cathode 50 after performing electrical work. Through the above-mentioned actions, electricity is generated.

[0040] In the above power generation reaction, the catalytic metal 34 functions as a catalyst in the reaction between hydrogen and oxide ions. The electronically conductive ceramics 31 are responsible for the conduction of electrons obtained by the reaction between hydrogen and oxide ions. The oxide ion conductive ceramics 32 are responsible for the conduction of oxide ions that reach the anode 30 from the solid electrolyte layer 40. The cathode catalyst 53 functions as a catalyst in the reaction in which oxide ions are produced from oxygen gas and electrons. The electronically conductive ceramics 51 are responsible for the conduction of electrons from an external electric circuit. The oxide ion conductive ceramics 52 are responsible for the conduction of oxide ions to the solid electrolyte layer 40.

[0041] Fuel cells can be fabricated by stacking each layer using powder materials and sintering them simultaneously. However, if there is a large difference in the shrinkage behavior of each layer during the sintering process, warping will occur, as shown in Figure 3. If a fuel cell is warped, stress will be generated in each fuel cell when multiple fuel cells are stacked to form a stack, making them more likely to crack.

[0042] As shown in the example of Figure 3, when the cell is placed on a flat surface, the distance between the two sides that are in contact with the surface is defined as distance B. The vertical distance from the apex of the warp to the flat surface is defined as distance A. The thickness of the cell is defined as L. In this case, the amount of warp is defined as T (%) = (AL) / B x 100 (%).

[0043] However, in the fuel cell 100 according to this embodiment, both the anode 30 and the cathode 50 are porous bodies formed of electronically conductive ceramics and oxygen ion conductive ceramics. In this configuration, the structural difference between the anode 30 and the cathode 50 is small. In addition, the first mixed layer 20 is provided on the anode side, and the second mixed layer 60 is provided on the cathode side. Furthermore, the first support 10 is provided on the anode side, and the second support 70 is provided on the cathode side. In this way, the fuel cell 100 has a symmetrical structure with the solid electrolyte layer 40 at the center. This reduces the difference in shrinkage behavior of each layer during the firing process, and suppresses warping. For example, the warping amount T (%) is less than 4%.

[0044] Furthermore, if the electronically conductive part of the anode and the electronically conductive part of the cathode are connected during the firing process, a short circuit between the electrodes may occur. However, in the fuel cell 100 according to this embodiment, the length a described in FIG. 1(a) is provided, so that the electronically conductive part of the anode and the electronically conductive part of the cathode are separated from each other. This makes it possible to suppress short circuits between the electrodes.

[0045] The smaller the a / b, the larger the effective power generation area. Therefore, it is preferable to set an upper limit for a / b. For example, it is preferable that a / b<1 / 10, more preferably a / b<1 / 20, and even more preferably a / b<1 / 50. For example, in a square cell of 100 mm×100 mm, if the spacing a is 1 mm, the area of ​​the cathode 50 is 98 mm×98 mm.

[0046] From the viewpoint of suppressing inter-electrode short circuits, the length a is preferably 1 mm or more, and more preferably 2 mm or more.

[0047] As described above, when the fuel cell 100 generates power, the oxidant gas flows to the cathode side. Therefore, when power is generated, the metal components on the cathode side may oxidize and expand, causing cracks. Therefore, it is preferable that the fuel cell 100 has a structure that can absorb the stress caused by the oxidation expansion. For example, it is preferable that the stress can be absorbed by the shape of the voids formed in each layer. Details will be described below.

[0048] 4 is a diagram illustrating the shape of a void 81 formed in the first support 10, the first mixed layer 20, and the anode 30, and the shape of a void 82 formed in the second support 70, the second mixed layer 60, and the cathode 50, in a cross section including the stacking direction. As illustrated in FIG. 4, the void 81 formed in the first support 10, the first mixed layer 20, and the anode 30 preferably has a substantially circular shape. On the other hand, the void 82 formed in the second support 70, the second mixed layer 60, and the cathode 50 preferably has a substantially elliptical shape.

[0049] Here, in a cross section cut in the stacking direction, the length in the direction in which each layer extends in a closed gap (hereinafter also referred to as the lateral direction) is defined as length c, and the height of the gap in the stacking direction is defined as height d. Length c is the maximum length in the lateral direction within one gap. Height d is the maximum height in the stacking direction within one gap.

[0050] The larger c / d is, the shorter the length of the material filling the gaps between the layers becomes. Therefore, the expansion in the lateral direction is mitigated, and the solid electrolyte layer 40 is less likely to crack. As illustrated in FIG. 5(a) and FIG. 5(b), the length L of the material filling the gaps in the lateral direction is L 1 +L 2 +L 3 +L 4 +L 5 The increase in length due to thermal expansion is calculated as ΔL=L×linear expansion coefficient. The increase in length due to oxidation is calculated as ΔL=L×oxidation expansion coefficient. In either case, the linear expansion coefficient and the oxidation expansion coefficient are physical property values, and are constants once the material is determined. Therefore, it can be seen that the increase in length ΔL is proportional to L. When comparing the elliptical void 82 in FIG. 5(a) with the circular void 81 in FIG. 5(b), it can be seen that the total material length L per unit length is smaller in FIG. 5(a) than in FIG. 5(b). Therefore, it can be seen that the increase in length ΔL is also smaller in the elliptical void 82. The smaller ΔL is, the more the mismatch with the solid electrolyte layer 40 is alleviated, and the more the solid electrolyte layer 40 is unlikely to crack.

[0051] Since oxidation expansion occurs on the cathode side and does not occur on the anode side, it is preferable that c / d on the cathode side is larger than c / d on the anode side. Therefore, it is preferable that the average value of each c / d for the multiple voids formed in the cathode 50 is larger than the average value of each c / d for the multiple voids formed in the anode 30. It is preferable that the average value of each c / d for the multiple voids formed in the second mixed layer 60 is larger than the average value of each c / d for the multiple voids formed in the first mixed layer 20. It is preferable that the average value of each c / d for the multiple voids formed in the second support 70 is larger than the average value of each c / d for the multiple voids formed in the first support 10.

[0052] Here, the method of measuring the length c and height d will be described. The actual voids are not ideal ellipses, but have an irregular peripheral shape. The cross section of the cell is observed with an SEM, and the length c and height d are measured from the SEM photograph. As illustrated in FIG. 6(a) and FIG. 6(b), the longest distance in the horizontal direction of the void portion is defined as c, and the longest distance in the vertical direction is defined as d. The cathode 50, the second mixed layer 60, and the second support 70 are all measured in the same manner, and the length c and height d of 20 or more voids are measured in each layer, and the average value is defined as the length c and height d of each layer. Using the average length c and height d, the value of c / d in each layer can be calculated. The length c and height d of the voids in the first support 10, the first mixed layer 20, and the anode 30 can also be measured by the same method.

[0053] From the standpoint of increasing c / d on the cathode side, the average value of c / d for each of the cathode 50, the second mixed layer 60, and the second support 70 preferably exceeds 1, more preferably exceeds 1.2, and even more preferably exceeds 1.5.

[0054] On the other hand, if c / d is too large, cracks may occur on the surface of the porous layer (cathode 50, second mixed layer 60, and second support 70) after firing. Therefore, it is preferable to set an upper limit for c / d. For example, the average value of c / d for each of the cathode 50, second mixed layer 60, and second support 70 is preferably less than 3, more preferably less than 2.5, and even more preferably less than 2.

[0055] If both the anode 30 and the cathode 50 are porous bodies formed of an electron conductive ceramic and an oxygen ion conductive ceramic, the structural difference between the anode 30 and the cathode 50 becomes small, and the anode 30 and the cathode 50 can be fired simultaneously. As a result, the adhesion of the anode 30 and the cathode 50 to the solid electrolyte layer 40 is improved, film peeling is suppressed, and the ohmic resistance of the entire fuel cell 100 is reduced.

[0056] In addition, the fuel cell 100 has a structure that is resistant to thermal shock, mechanical shock, and the like, since it includes the first support 10 and the second support 70 that are mainly composed of metal. In addition, the first mixed layer 20 contains the metal material 21 and the ceramic material 22, and therefore has both the material properties of metal and the material properties of ceramic. Therefore, the first mixed layer 20 has high adhesion to the first support 10 and also has high adhesion to the anode 30. From the above, it is possible to suppress interlayer peeling between the first support 10 and the anode 30. The second mixed layer 60 contains the metal material 61 and the ceramic material 62, and therefore has both the material properties of metal and the material properties of ceramic. Therefore, the second mixed layer 60 has high adhesion to the second support 70 and also has high adhesion to the cathode 50. From the above, it is possible to suppress interlayer peeling between the second support 70 and the cathode 50.

[0057] In the fuel cell 100, the oxide ion conductive ceramic 33 is supported on the porous body of the anode 30. In this structure, the porous body is first formed by firing, and then the oxide ion conductive ceramic 33 is impregnated and fired at a low temperature. Therefore, even if the oxide ion conductive ceramic 32 and the oxide ion conductive ceramic 33 do not have the same composition, the inter-oxide reaction is suppressed. This allows greater freedom in selecting an oxide suitable for the composite catalyst as the oxide ion conductive ceramic 33.

[0058] Similarly, in the fuel cell 100, the cathode catalyst 53 is supported on the porous body of the cathode 50. In this structure, the porous body is first formed by firing, and then the cathode catalyst 53 is impregnated and fired at a low temperature. Therefore, even if the oxide ion conductive ceramics 52 and the cathode catalyst 53 do not have the same composition, the inter-oxide reaction is suppressed. This allows greater freedom in selecting a preferred oxide for the cathode catalyst 53.

[0059] In addition, the porosity of the first support 10, the porosity of the first mixed layer 20, and the porosity of the anode 30 preferably satisfy the relationship (first support 10>first mixed layer 20>anode 30). The porosity of the second support 70, the porosity of the second mixed layer 60, and the porosity of the cathode 50 preferably satisfy the relationship (second support 70>second mixed layer 60>cathode 50). When this relationship is satisfied, sufficient gas permeability is obtained in the support. In the electrode, by having a relatively low porosity, high electronic conductivity and high oxide ion conductivity are obtained while maintaining gas permeability. In the mixed layer, gas permeability is obtained, and a contact area with the support is obtained, thereby obtaining adhesion with the support.

[0060] Furthermore, it is preferable that the thicknesses of the first support 10, the first mixed layer 20, and the anode 30 satisfy the relationship: first support 10>first mixed layer 20>anode 30, and that the thicknesses of the second support 70, the second mixed layer 60, and the cathode 50 satisfy the relationship: second support 70>second mixed layer 60>cathode 50. By satisfying these relationships, most (e.g., 80% or more) of the volume of the entire fuel cell 100 is made of metal material, and this provides the effect of improving mechanical strength such as rapid temperature increase / decrease and flexibility.

[0061] Since the anode reaction and the cathode reaction are chemical reactions that occur on the surface of the catalyst, it is preferable that the catalyst has a large surface area per unit volume in order to promote the chemical reactions. For example, the average crystal grain size of the anode catalyst (oxide ion conductive ceramics 33 and catalytic metal 34) and the cathode catalyst 53 is preferably 100 nm or less, more preferably 80 nm or less, and even more preferably 50 nm or less.

[0062] If there is a large variation in the thicknesses of the anode 30 and the cathode 50, the first mixed layer 20 and the second mixed layer 60, and the first support 10 and the second support 70, the structure of the fuel cell 100 approaches an asymmetric structure, and the thermal stress between the upper and lower materials is not offset, which may cause warping of the fuel cell 100. Therefore, for example, it is preferable that the thickness of the anode 30 is within ±50% of the thickness of the cathode 50, the thickness of the first mixed layer 20 is within ±50% of the thickness of the second mixed layer 60, and the thickness of the first support 10 is within ±50% of the thickness of the second support 70.

[0063] The following describes a method for manufacturing the fuel cell 100. Figure 7 is a diagram illustrating an example of the flow of the method for manufacturing the fuel cell 100.

[0064] (Preparation process of first support material and second support material) As the support material, a metal powder (for example, a particle size of 10 μm to 100 μm), a plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), a solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), a dissipation material (organic matter), and a binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. The support material is used as a material for forming a support. The volume ratio of the organic component (dissipation material, binder solid content, plasticizer) to the metal powder is, for example, in the range of 1:1 to 20:1, and the amount of the organic component is adjusted depending on the porosity. In the first support material, circular resin particles are used as the dissipation material. In the second support material, elliptical resin particles are used as the dissipation material.

[0065] (Preparation process of first mixed layer material and second mixed layer material) As the material for the mixed layer, ceramic material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the ceramic material 22, 62, small particle size metal material powder (for example, particle size 1 μm to 10 μm) which is the raw material of the metal material 21, 61, solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), dissipation material (organic matter), and binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. The volume ratio of the organic component (dissipation material, binder solid content, plasticizer) to the ceramic material powder and metal material powder is, for example, in the range of 1:1 to 5:1, and the amount of the organic component is adjusted depending on the porosity. The pore size of the voids is controlled by adjusting the particle size of the dissipation material. The ceramic material powder may contain an electron conductive material powder and an oxide ion conductive material powder. In this case, the volume ratio of the electron conductive material powder to the oxide ion conductive material powder is preferably in the range of, for example, 1:9 to 9:1. Even if an electrolyte material such as ScYSZ or GDC is used instead of the electron conductive material, there is no peeling at the interface, and a cell can be fabricated. However, from the viewpoint of reducing the ohmic resistance, it is preferable to mix the electron conductive material with a metal powder. In the first mixed layer material, circular resin particles are used as the dissipating material. In the second mixed layer material, elliptical resin particles are used as the dissipating material.

[0066] (Anode material manufacturing process) As the anode material, a ceramic material powder constituting the porous body, a solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), a plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), a dissipating material (organic material), and a binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. As the ceramic material powder constituting the porous body, an electron conductive material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the electron conductive ceramic 31, an oxide ion conductive material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the oxide ion conductive ceramic 32, etc. may be used. The volume ratio of the organic components (dissipating material, binder solids, plasticizer) to the electron conductive material powder is, for example, in the range of 1:1 to 5:1, and the amount of the organic components is adjusted depending on the porosity. The pore size of the voids is controlled by adjusting the particle size of the dissipating material. The volume ratio of the electron conductive material powder to the oxide ion conductive material powder is, for example, in the range of 1:9 to 9:1. In the anode material, circular resin particles are used as the dissipating material.

[0067] (Cathode material manufacturing process) As the cathode material, a ceramic material powder constituting the porous body, a solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), a plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), a dissipating material (organic material), and a binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. As the ceramic material powder constituting the porous body, an electron conductive material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the electron conductive ceramics 51, an oxide ion conductive material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the oxide ion conductive ceramics 52, etc. may be used. The volume ratio of the organic components (dissipating material, binder solids, plasticizer) to the electron conductive material powder is, for example, in the range of 1:1 to 5:1, and the amount of the organic components is adjusted depending on the porosity. The pore size of the voids is controlled by adjusting the particle size of the dissipating material. The volume ratio of the electron conductive material powder to the oxide ion conductive material powder is, for example, in the range of 1:9 to 9:1. When the anode material and the cathode material are the same, the anode material may be used as the cathode material. In the cathode material, elliptical resin particles are used as the dissipating material.

[0068] (Electrolyte layer material manufacturing process) As the material for the electrolyte layer, oxide ion conductive material powder (e.g., ScYSZ, YSZ, GDC, etc., with a particle size of 10 nm to 1000 nm), solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), plasticizer (e.g., adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), and binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. The volume ratio of the organic components (binder solids, plasticizer) to the oxide ion conductive material powder is, for example, in the range of 6:4 to 3:4.

[0069] (Firing process) First, a first support material is applied onto a PET (polyethylene terephthalate) film to prepare a first support green sheet. A first mixed layer material is applied onto another PET film to prepare a first mixed layer green sheet. An anode material is applied onto another PET film to prepare an anode green sheet. An electrolyte layer material is applied onto another PET film to prepare an electrolyte layer green sheet. For example, a plurality of first support green sheets, one first mixed layer green sheet, one anode green sheet, and one electrolyte layer green sheet are laminated in this order. The peripheries of the first support green sheet, the first mixed layer green sheet, the anode green sheet, and the electrolyte layer green sheet are aligned. The laminate may be cut to a predetermined size to match the respective peripheries. Then, a slurry of a cathode electrode material is printed onto the electrolyte green sheet. After drying, a slurry of a second mixed layer material is printed onto the cathode electrode material. After drying, the second support material is thickly coated on the second mixed layer material by repeatedly printing and drying the slurry of the second support material several times. When printing the slurry of the cathode electrode material, the slurry of the second mixed layer material, and the slurry of the second support material, the slurry is centrifuged under appropriate conditions before printing in order to orient the elliptical resin particles in the length direction horizontally to the printing direction. The slurry of the cathode electrode material, the slurry of the second mixed layer material, and the slurry of the second support material are printed inward from the outer periphery of the electrolyte green sheet. Thereafter, the slurry is printed in an atmosphere in which the oxygen partial pressure is increased to 10 -16 The material is fired in a reducing atmosphere of 1 atm or less at a temperature range of about 1100°C to 1300°C. This produces a cell including the first support 10, the first mixed layer 20, the porous body of the anode 30, the solid electrolyte layer 40, the porous body of the cathode 50, the second mixed layer 60, and the second support 70. The reducing gas flowing in the furnace is H 2 (hydrogen) into non-flammable gas (Ar (argon), He (helium), N 2 It may be a gas diluted with H 2 For safety reasons, it is preferable to set an upper limit up to the explosion limit. For example, H 2In the case of a mixture of H and Ar, 2 The concentration is preferably 4% by volume or less.

[0070] (Anode impregnation process) Next, the raw materials of the oxide ion conductive ceramics 33 and the catalytic metal 34 are impregnated into the porous body of the anode 30. For example, nitrates or chlorides of Zr, Y, Sc, Ce, Gd, and Ni are dissolved in water or alcohols (ethanol, 2-propanol, methanol, etc.) so that Gd-doped ceria or Sc, Y-doped zirconia and Ni are produced when fired at a predetermined temperature in a reducing atmosphere, and the solution is impregnated into the porous body of the anode 30, dried, and heat-treated a required number of times.

[0071] (Cathode impregnation process) Next, PrO x The cathode catalyst 53 is impregnated into the porous body of the cathode 50. x When using, for example, nitrate or chloride of Pr is dissolved in water or alcohol (ethanol, 2-propanol, methanol, etc.), impregnated into the porous body of the cathode 50, dried, and heat treatment is repeated a required number of times. When using LSM as the cathode catalyst 53, for example, nitrate or chloride of Sr, nitrate or chloride of La, and nitrate or chloride of Mn are dissolved in water or alcohol (ethanol, 2-propanol, methanol, etc.), impregnated into the half-cell, dried, and heat treatment is repeated a required number of times. When using LSC as the cathode catalyst 53, for example, nitrate or chloride of Sr, nitrate or chloride of La, and nitrate or chloride of Co are dissolved in water or alcohol (ethanol, 2-propanol, methanol, etc.), impregnated into the half-cell, dried, and heat treatment is repeated a required number of times.

[0072] According to the manufacturing method of this embodiment, when the anode 30 and the cathode 50 are fired, both of them use an electron conductive material and an oxide ion conductive material, so that the structural difference between the porous body of the anode 30 and the porous body of the cathode 50 is small. In addition, the first mixed layer 20 is fired on the anode side, and the second mixed layer 60 is fired on the cathode side. Furthermore, the first support 10 is fired on the anode side, and the second support 70 is fired on the cathode side. In this way, the fuel cell 100 has a symmetrical structure with the solid electrolyte layer 40 at the center. Thereby, the difference in the shrinkage behavior of each layer during the firing process is small, and warping is suppressed. For example, the warping amount T (%) is less than 4%.

[0073] In addition, the slurry of the cathode electrode material, the slurry of the second mixed layer material, and the slurry of the second support material are printed inward from the outer periphery of the electrolyte green sheet, which separates the electronically conductive part of the anode side from the electronically conductive part of the cathode side, thereby preventing short circuits between the electrodes.

[0074] Also, by making the shape of the anode-side vanishing material different from that of the cathode-side vanishing material, the c / d on the cathode side can be made larger than the c / d on the anode side. For example, the average value of each c / d for the multiple voids formed in the cathode 50 can be made larger than the average value of each c / d for the multiple voids formed in the anode 30. The average value of each c / d for the multiple voids formed in the second mixed layer 60 can be made larger than the average value of each c / d for the multiple voids formed in the first mixed layer 20. The average value of each c / d for the multiple voids formed in the second support 70 can be made larger than the average value of each c / d for the multiple voids formed in the first support 10.

[0075] In addition, since the structural difference between the porous body of the anode 30 and the porous body of the cathode 50 is reduced, the anode 30 and the cathode 50 can be fired simultaneously. As a result, the adhesion of the anode 30 and the cathode 50 to the solid electrolyte layer 40 is improved, film peeling is suppressed, and the ohmic resistance of the entire fuel cell 100 is reduced.

[0076] In addition, since the material for the first mixed layer contains a metal material and a ceramic material, the first mixed layer 20 after firing contains a metal material 21 and a ceramic material 22. As a result, the first mixed layer 20 has both the material properties of metal and the material properties of ceramic. Therefore, during the firing process, it is possible to suppress interlayer peeling between the first support 10 and the anode 30. Since the material for the second mixed layer contains a metal material and a ceramic material, the second mixed layer 60 after firing contains a metal material 61 and a ceramic material 62. As a result, the second mixed layer 60 has both the material properties of metal and the material properties of ceramic. Therefore, during the firing process, it is possible to suppress interlayer peeling between the second support 70 and the cathode 50.

[0077] It is preferable to adjust the amount of the dissipation material in the support material, the mixed layer material, the anode material, and the cathode material so that the relationship between the porosity of the first support 10, the porosity of the first mixed layer 20, and the porosity of the anode 30 is (first support 10>first mixed layer 20>anode 30), and the relationship between the porosity of the second support 70, the porosity of the second mixed layer 60, and the porosity of the cathode 50 is (second support 70>second mixed layer 60>cathode 50). By establishing this relationship, sufficient gas permeability is obtained in the support. In the electrode, the electrode becomes dense and high oxide ion conductivity is obtained. In the mixed layer, gas permeability is obtained, and a contact area with the support is obtained, thereby obtaining adhesion to the support.

[0078] In addition, in the manufacturing method according to the present embodiment, the porous body is first formed by firing, and then the composite catalyst is impregnated and fired at a low temperature (for example, 850° C. or lower). This suppresses the reaction between the porous body of the anode 30 and the anode catalyst. Also, this suppresses the reaction between the porous body of the cathode 50 and the cathode catalyst. This increases the freedom to select the anode catalyst and the cathode catalyst. EXAMPLES

[0079] A fuel cell 100 was produced according to the manufacturing method according to the above embodiment.

[0080] Example 1 The support material was SUS (stainless steel) powder. The electrolyte layer was ScYSZ. The anode was made of LaCrO 3 The cathode is made of an oxide-ion conductive ceramic material, ScYSZ, and the cathode is made of an electron conductive ceramic material, LaCrO. 3 The oxide-ion conductive ceramics used were ScYSZ, and the ceramic material for the mixed layer was LaCrO 3 The metallic material used for the mixed layer was SUS.

[0081] The support green sheet, mixed layer green sheet, anode green sheet, and electrolyte green sheet were laminated in this order, and the cathode material was printed and dried, the mixed layer material was printed and dried, and the support material was printed and dried. After that, a firing process was performed to produce a single cell with a symmetrical structure. In order to adjust c / d, the length direction of the elliptical vanishing material in the cathode material, the cathode side mixed layer material, and the cathode side support material was R, and the short direction was r, and a resin with R / r=1.5 / 1 was used. The size of the cell was 100mm x 100mm, and a gap of 1mm was taken from the outer periphery when printing the cathode side. In other words, the opposite side was printed with an area of ​​98mm x 98mm. Several cells were produced, and one of them was subjected to cross-sectional SEM observation. The average c / d of the cathode, second mixed layer, and second support measured from the SEM image was 1.5. As sintering progressed, the voids created by the lost material contracted isotropically, which is thought to have resulted in R / r=c / d=1.5. On the other hand, spherical lost material was used on the anode side, which contracted isotropically as sintering progressed, which is thought to have resulted in R / r=c / d=1. The anode side was impregnated with Ni and GDC over an area of ​​98mm x 98mm, and the cathode side was impregnated with LSM over an area of ​​98mm x 98mm.

[0082] Warping was evaluated and found to be less than 1%. This is believed to be due to the symmetrical structure. Additionally, no short circuits occurred between the electrodes. This is believed to be due to the spacing provided from the outer periphery when printing the cathode side. Power generation evaluation was performed with one cell sandwiched between the upper and lower interconnectors. Additionally, there was no current collector between the cell and the interconnector, which were connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement, and the ohmic resistance of this cell was found to be 0.3 Ω cm 2 and the reaction resistance is 0.7 Ω cm 2 The effective power generation area utilization rate of the cell was (98×98) / (100×100)=96%, and the larger the effective area, the higher the current that could be extracted from the cell, so the current that flowed when the terminal voltage was 0.9V was 19.1A.

[0083] Example 2 In Example 2, when the cathode material, the mixed layer material, and the support material were printed, a distance of 2 mm was provided from the outer periphery. In other words, printing was performed in an area of ​​96 mm x 96 mm. Other conditions were the same as in Example 1. A number of cells were produced, and one of them was subjected to cross-sectional SEM observation. The average c / d of the cathode, the second mixed layer, and the second support measured from the SEM image was 1.5. As in Example 1, the dissipation material used on the cathode side was an elliptical resin with R / r = 1.5 / 1, so the voids were isotropically shrunk, and as a result, c / d was thought to be 1.5. As the dissipation material on the anode side was a spherical resin with R / r = 1, so the voids were isotropically shrunk, and as a result, c / d was thought to be 1.

[0084] Warping was evaluated and found to be less than 1%. This is believed to be due to the symmetrical structure. Additionally, no short circuits occurred between the electrodes. This is believed to be due to the spacing provided from the outer periphery when printing the cathode side. Power generation evaluation was performed with one cell sandwiched between the upper and lower interconnectors. Additionally, there was no current collector between the cell and the interconnector, which was connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement, and the ohmic resistance of this cell was found to be 0.3 Ω·cm 2 and the reaction resistance is 0.7 Ω cm 2 The effective power generation area utilization rate of the cell was (96 x 96) / (100 x 100) = 92%, and the larger the effective area, the higher the current that could be extracted from the cell, so the current that flowed when the terminal voltage was 0.9V was 18.3A.

[0085] Example 3 In order to adjust c / d, a circular resin was used as the vanishing material used in the printing slurry, instead of an elliptical resin. Other conditions were the same as in Example 2. A number of cells were produced, and one of them was subjected to cross-sectional SEM observation. The average c / d of the cathode, the second mixed layer, and the second support measured from the SEM image was 1. In order to control c / d, the vanishing material used in Example 3 was changed to a spherical resin with R / r=1. As sintering progressed, the voids generated by the vanishing material contracted isotropically, so it is considered that R / r=c / d=1. Similarly, the anode side was changed to a spherical resin vanishing material with R / r=1. As sintering progressed, the voids generated by the vanishing material contracted isotropically, so it is considered that R / r=c / d=1.

[0086] Warping was evaluated and found to be less than 1%. This is believed to be due to the symmetrical structure. Additionally, no short circuits occurred between the electrodes. This is believed to be due to the spacing provided from the outer periphery when printing the cathode side. Power generation evaluation was performed with one cell sandwiched between the upper and lower interconnectors. Additionally, there was no current collector between the cell and the interconnector, which was connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement, and the ohmic resistance of this cell was found to be 0.3 Ω·cm 2 and the reaction resistance is 0.7 Ω cm 2 The effective power generation area utilization rate of the cell was (96 x 96) / (100 x 100) = 92%, and the larger the effective area, the higher the current that could be extracted from the cell, so the current that flowed when the terminal voltage was 0.9V was 18.3A.

[0087] Example 4 A half cell in which the support green sheet, the mixed layer green sheet, the anode green sheet, and the electrolyte green sheet were laminated in this order was fired. On the electrolyte layer of the fired half cell, the cathode material was printed and dried, the mixed layer material was printed and dried, and the support material was printed and dried. Then, a firing process was performed to produce a single cell having a symmetrical structure. In order to adjust c / d, the dimensions of the vanishing material used in the printing slurry were adjusted. The long direction of the ellipse was R, the short direction was r, and a resin with R / r=2 / 1 was used. The other conditions were the same as in Example 1. A number of cells were produced, and one of them was subjected to cross-sectional SEM observation. The average c / d of the cathode, the second mixed layer, and the second support measured from the SEM image was 2. Since the vanishing material on the anode side was a spherical resin with R / r=1, it is considered that the voids were unidirectionally shrunk, and as a result, c / d became 1.

[0088] Warping was evaluated and found to be less than 1%. This is believed to be due to the symmetrical structure. Additionally, no short circuits occurred between the electrodes. This is believed to be due to the spacing provided from the outer periphery when printing the cathode side. Power generation evaluation was performed with one cell sandwiched between the upper and lower interconnectors. Additionally, there was no current collector between the cell and the interconnector, which were connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement, and the ohmic resistance of this cell was found to be 0.3 Ω cm 2 and the reaction resistance is 0.7 Ω cm 2 The effective power generation area utilization rate of the cell was (96 x 96) / (100 x 100) = 92%, and the larger the effective area, the higher the current that could be extracted from the cell, so the current that flowed when the terminal voltage was 0.9V was 18.3A.

[0089] Example 5 In order to adjust c / d, the dimensions of the dissipation material used in the printing slurry were adjusted. The long direction of the ellipse was R, the short direction was r, and a resin with R / r=2.5 / 1 was used. Several cells were made, and one of them was subjected to cross-sectional SEM observation. The average c / d of the cathode, the second mixed layer, and the second support measured from the SEM image was 2.5. Since a spherical resin with R / r=1 was used for the dissipation material on the anode side, it is considered that the voids were isotropically shrunk, and as a result, c / d became 1. The other conditions were the same as in Example 4.

[0090] Warping was evaluated and found to be less than 1%. This is believed to be due to the symmetrical structure. Additionally, no short circuits occurred between the electrodes. This is believed to be due to the spacing provided from the outer periphery when printing the cathode side. Power generation evaluation was performed with one cell sandwiched between the upper and lower interconnectors. Additionally, there was no current collector between the cell and the interconnector, which were connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement, and the ohmic resistance of this cell was found to be 0.3 Ω cm 2 and the reaction resistance is 0.7 Ω cm 2 The effective power generation area utilization rate of the cell was (96 x 96) / (100 x 100) = 92%, and the larger the effective area, the higher the current that could be extracted from the cell, so the current that flowed when the terminal voltage was 0.9V was 18.3A.

[0091] Comparative Example 1 When printing the cathode side, no space was taken from the outer circumference. In other words, the opposite side was printed with an area of ​​100 mm x 100 mm. Other conditions were the same as in Example 1. After firing, the support layers on both sides were connected with a tester, and as a result of measurement, it was confirmed that the electrodes were short-circuited. In addition, when the outer circumference of the cell was examined with a microscope, the metal parts on both sides were observed to be connected, and it is considered that the metal parts were connected during the sintering process. It was not possible to evaluate the power generation of such a cell. Several cells were produced, and one of them was observed by cross-sectional SEM observation. The average c / d of the cathode, second mixed layer, and second support measured from the SEM image was 1.5. Since the disappearance material on the anode side was a spherical resin with R / r=1, it is considered that the gaps were isotropically shrunk, and as a result, c / d became 1.

[0092] Comparative Example 2 A half cell was sintered, in which the support green sheet, mixed layer green sheet, anode green sheet, and electrolyte green sheet were laminated in this order. The cathode material was printed and dried on the electrolyte layer of the sintered half cell, the mixed layer material was printed and dried, and the support material was printed and dried. After that, a sintering process was performed to produce a single cell with a symmetrical structure. The size of the single cell was 100 mm x 100 mm, and no sealant was applied to the outer periphery of the cell. The anode side was impregnated with Ni and GDC over an area of ​​96 mm x 96 mm. Next, the cathode side was printed with LSM over an area of ​​96 mm x 96 mm, and sintering was performed at a temperature of 900 ° C or less to suppress oxidation of the metal support. The structure of the single cell was asymmetric, and the warpage was evaluated to be 4%. When the power generation evaluation was performed, one cell was sandwiched between the upper and lower interconnectors. In addition, on the anode side, there was no current collector between the cell and the interconnector, and they were connected by laser welding. The cathode side was made of ceramic material only, and it was not possible to connect it to the interconnector by welding. This was presumably due to the large warping. Therefore, a current collector was placed between the cell and the interconnector, and evaluation was performed in this sandwiched state. As a result of the power generation evaluation, each resistance value was separated by impedance measurement, and the ohmic resistance of this cell was found to be 0.7 Ω cm 2and the reaction resistance is 0.7 Ω cm 2 Compared to Examples 1 to 4, the cell could not be fixed by welding on the cathode side, and when the current collector was sandwiched, the contact was poor and the ohmic resistance increased significantly. The effective power generation area utilization rate of the cell was (96×96) / (100×100)=92%. In addition, the current that flowed when the terminal voltage was 0.9V was 13.2A, and although the effective power generation area was the same as in Example 2, the ohmic resistance increased, and the current that could be extracted by power generation at the same terminal voltage was significantly reduced.

[0093] The results of Examples 1 to 5 and Comparative Examples 1 and 2 are shown in Tables 1 and 2. [Table 1] [Table 2]

[0094] (C / D rating) In order to evaluate the susceptibility of the electrolyte to cracking, the single cells of Examples 2 to 5 were subjected to heat treatment at a temperature of 800°C or higher. If the electrolyte cracked after the heat treatment, gas leakage was detected by gas leakage measurement. FIG. 8 shows the relationship between the heat treatment temperature at which gas leakage was detected and the c / d value. It was found that the larger the c / d, the higher the heat treatment temperature that could be tolerated. In other words, it can be seen that the larger the c / d, the less likely the electrolyte is to crack.

[0095] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]

[0096] 10 First support 20 1st mixed layer 21 Metal materials 22 Ceramic Materials 30 Anode 31 Electronically Conductive Ceramics 32 Oxide-ion conductive ceramics 33 Oxide-ion conductive ceramics 34 Catalytic Metals 40 Solid electrolyte layer 50 Cathode 51 Electronically Conductive Ceramics 52 Oxide-ion conductive ceramics 53 Cathode catalyst 60 2nd mixed layer 70 Second support 100 fuel cell

Claims

1. a solid electrolyte layer including a solid oxide having oxide ion conductivity; an anode provided on a first surface of the solid electrolyte layer, the anode having a porous body including an electron conductive ceramic and an oxide ion conductive ceramic, the porous body having an anode catalyst; a first mixed layer provided on a surface of the anode opposite to the solid electrolyte layer and having a structure in which a metal material and a ceramic material are mixed; a first support body mainly composed of a metal, the first support body being provided on a surface of the first mixed layer opposite to the solid electrolyte layer; a cathode provided on a second surface of the solid electrolyte layer, the cathode having a porous body including an electron conductive ceramic and an oxide ion conductive ceramic, the porous body having a cathode catalyst; a second mixed layer provided on a surface of the cathode opposite to the solid electrolyte layer and having a structure in which a metal material and a ceramic material are mixed; a second support body provided on a surface of the second mixed layer opposite to the solid electrolyte layer and mainly composed of a metal; A solid oxide fuel cell, characterized in that one of the outer periphery of the anode, the first mixed layer, and the first support, and the outer periphery of the cathode, the second mixed layer, and the second support, is located inward relative to the other.

2. 2. The solid oxide fuel cell according to claim 1, wherein one of the outer periphery of the anode, the first mixed layer, and the first support, and the outer periphery of the cathode, the second mixed layer, and the second support, is located 1 mm or more inward from the other.

3. The solid oxide fuel cell has a generally rectangular shape in a plan view, 3. The solid oxide fuel cell according to claim 1, wherein a / b is 1 / 10 or less, where a is the length from the outer periphery of the anode, the first mixed layer, and the first support to the outer periphery of the cathode, the second mixed layer, and the second support, and b is the length of one side of the solid oxide fuel cell.

4. 4. The solid oxide fuel cell according to claim 1, wherein the outer periphery of the cathode, the second mixed layer and the second support is located inward relative to the outer periphery of the anode, the first mixed layer and the first support.

5. 5. The solid oxide fuel cell according to claim 1, wherein the amount of warping of the solid oxide fuel cell is less than 4%.

6. In a cross section including the stacking direction, when the length of a gap in each layer in the extending direction of each layer is defined as length c and the height in the stacking direction is defined as height d, the average value of c / d of each gap of the cathode is greater than the average value of c / d of each gap of the anode; the average value of c / d of each gap in the second mixed layer is greater than the average value of c / d of each gap in the first mixed layer; 6. A solid oxide fuel cell according to claim 1, wherein the average value of c / d of each gap of the second support is greater than the average value of c / d of each gap of the first support.

7. 7. The solid oxide fuel cell according to claim 6, wherein the average value of c / d of each of the voids in the cathode, the second mixed layer, and the second support is greater than 1 and less than 3.

8. the anode catalyst is Ni and GDC; The cathode catalyst is PrO x 8. The solid oxide fuel cell according to claim 1, further comprising at least one of LSM, LSC and GDC.

9. 9. The solid oxide fuel cell according to claim 1, wherein the anode catalyst and the cathode catalyst each have an average particle size of 100 nm or less.

10. a relationship of the porosity of the first support, the porosity of the first mixed layer, and the porosity of the anode is the first support>the first mixed layer>the anode, 10. The solid oxide fuel cell according to claim 1, wherein the relationship between the porosity of the second support, the porosity of the second mixed layer, and the porosity of the cathode is: second support > second mixed layer > cathode.

11. a thickness of the first support, a thickness of the first mixed layer, and a thickness of the anode satisfy the following relationship: first support>first mixed layer>anode; 11. The solid oxide fuel cell according to claim 1, wherein a relationship is established among a thickness of the second support, a thickness of the second mixed layer, and a thickness of the cathode: second support > second mixed layer > cathode.

12. preparing a laminate including a support green sheet containing a metal powder, a mixed layer green sheet containing a ceramic material powder and a metal material powder, an electrode green sheet containing an electron conductive ceramic material powder and an oxide ion conductive ceramic material powder, and an electrolyte green sheet containing a solid oxide material powder having oxide ion conductivity; a step of printing a slurry containing an electron-conductive ceramic material powder and an oxide-ion-conductive ceramic material powder, a slurry containing a ceramic material powder and a metal material powder, and a slurry containing a metal powder on the inner side of the outer periphery of the electrolyte green sheet, and then firing the printed material.

Citation Information

Patent Citations

  • fuel cell

    JP2004512651A

  • Method for making electrochemical apparatus for recovery of oxygen

    JP2006321706A

  • solid oxide fuel cell

    JP2008502113A

  • Metal-supported electrochemical cell and method for manufacturing the same

    JP2013501330A

  • Metal support cell support structure

    JP2020021646A